2020
DOI: 10.1007/s00213-020-05492-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between behavioral inhibition and neural alcohol cue-reactivity in ADHD and alcohol use disorder

Abstract: Rationale Compared to the general population, adult Attention-Deficit / Hyperactivity Disorder (ADHD) is more prevalent in patients with Alcohol Use Disorder (AUD). Impaired behavioral inhibition is a common characteristic in both ADHD and AUD. Relapse risk is increased in patients with AUD and comorbid, untreated ADHD and in AUD patients with increased neural cuereactivity. Objectives In this study, we examined the interaction between neural correlates of behavioral inhibition and alcohol cuereactivity with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 93 publications
1
17
0
Order By: Relevance
“…Participants were recruited from the Adult ADHD Inpatient Program at the Median Clinics for Psychosomatics, Bad Dürkheim, Germany (sample A) and from the Adult ADHD Outpatient Clinics and the Department of Addictive Behavior and Addiction Medicine at the Central Institute of Mental Health, Mannheim, Germany (sample B) after obtaining informed consent. Individuals of sample B also participated in the AlcADHD study (for details please see [9]). Study procedures were approved by the local Ethics Committee (2015-571 N-MA, 2013-530 N-MA).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were recruited from the Adult ADHD Inpatient Program at the Median Clinics for Psychosomatics, Bad Dürkheim, Germany (sample A) and from the Adult ADHD Outpatient Clinics and the Department of Addictive Behavior and Addiction Medicine at the Central Institute of Mental Health, Mannheim, Germany (sample B) after obtaining informed consent. Individuals of sample B also participated in the AlcADHD study (for details please see [9]). Study procedures were approved by the local Ethics Committee (2015-571 N-MA, 2013-530 N-MA).…”
Section: Participantsmentioning
confidence: 99%
“…All individuals were fluent in German. All patients with ADHD underwent a standardized diagnostic procedure of adult ADHD according to German Guidelines [10,11], individuals of sample B (ADHD, Alcohol Use Disorder [AUD], healthy controls) underwent a standardized study diagnostic assessment [9]. ADHD was diagnosed by senior psychiatrists experienced in adult ADHD (B.A., E.S).…”
Section: Participantsmentioning
confidence: 99%
“…Interference inhibition did not lead to significant differences between ADHD or AUD and HC, although previous studies reported hypoactivation in networks related to attention, such as the anterior cingulate cortex, sensory and parietal regions ( 35 ), for ADHD compared to HC. In a different paradigm, our workgroup also did not observe neural alterations during interference inhibition in AUD compared to ADHD or HC, when considering only the neutral condition ( 52 ).…”
Section: Discussionmentioning
confidence: 76%
“…It should also be noted that some studies apply interference inhibition task that are combined with salient substance-related stimuli. The interaction of both, task and stimulus, leads to more pronounced results ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation